ETNOMATEMATIKA PADA AKTIVITAS PETANI KAKAO DESA TEMUASRI SEMPU BANYUWANGI SEBAGAI BAHAN AJAR SISWA - Indri Aprilianti; Sunardi Sunardi; Erfan Yudianto (FKIP Universitas Jember, 2019)
The purpose of this study is to explore ethnomatematics in the activities of cocoa farmers to create the teaching materials for students in the form of the packages of test. The type of research was qualitative research with ethnographic approaches. The data collection method used were observation and interview. The research subjects were six people. The ethnomatematics included the activity of counting, measuring, and designing. This study focused on determining the estimated number of trees based on its distance and area by using stakes (patok), determining the fertilization model based on the fertilization time and the planting age, determining the number of workers based on the land area, and estimating yields. The emerging mathematical concepts were comparison and social arithmetic.